Manajemen Psikotes Berbasis Android - Puput Mulyono; Singgih Purnomo (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The aim of this research is to create an Android-based cell mental check utility in which this software may be used as a medium to make it greater efficient and less complicated for people to prepare for the psychological test. The method in this research is collecting data regarding psychological tests, through writings and books, starting from question statements to searching for results that will be the output of this application. The result of this studies is an Android-based totally mental take a look at software that may be used on smartphones. the belief of this research is that an Android-based psychological take a look at application makes wearing out assessments less complicated and extra efficient due to the truth it may be accessed via a cellphone.